The Denotative and Connotative Meaning in Song Lyrics Entitled “Sandals” by Khai Dreams - Salam, Alifsya; Sakinah, R. Myrna Nur (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2024)
Music is a personal representation of oneself that utter their meaning in harmonic way. Music can utter sign that was born and inherit the complex characteristic of object manifested directly within context of being represented. Messages manifest throughout every music come from extraction of cultural phenomenon and belief to make the identity of music become vulnerable. Love contains emotional feeling of person to another person in showing their care as a mean to build relationship close towards each other. Songs entitled “Sandals” by Khai Dreams tells a relation of love with a struggle to achieve his everlasting moment with his beloved one but the situation make it hard to deal for him that always put him in a one-sided love. This study use lyrics song of “Sandals” as a primary data and further to be analyzed according to its descriptive content of denotation, connotation and the myth around the object area. The denotative meaning in this song tell the story of a man resembled as “I”, “me” and “my” in a struggle to keep his love fulfilled within those long time of wait. The connotative meaning in this song expand the background of meaning within denotative perspective that the man anticipation of love event somehow feels like a journey that he never expect to make it out even with the rival of love he faced, an unperfect love he deal towards his loved one and his sincerity towards his loved one over his struggle.